Caso de estudio: exportación de aceite de aguaje para el cuidado de la piel al mercado de Estados Unidos - Garrido Alvarado, Camila Del Rosario (2020)
The beauty market is one of the most competitive in the United States with around $17.7 billion in annual revenue, of which 45% belongs to the skin care market. Within the skincare category, the essential oil market is valued at $6.4 billion and is expected to reach $7700 by 2020, approximately 200 types of essential oils are sold in the United States. The largest exporter of essential oils is France, with a market share of 18.3%, followed by China and the United States with 13.54% and 12.21% respectively. The United States is not only one of the leading exporters of essential oils, but also the first importing country, with 23.5% of the total imported, followed by France with 22%. Trends in skin care are shifting towards a natural and guided approach to skin prevention and protection, today's consumer is educated and informs more about the content and provenance of the products he uses, he is cautious when placing pro ducts on their skin, prefer to consume natural and organic products that are free of chemical contents that can damage the skin over time. Likewise, products made from fruits, seeds and herbs are the most prestigious in the market for their healing and preventive factors, in addition to their great contributions in vitamins and minerals. In the present work, a study is carried out for the commercialization of water oil for skin care to the U.S. market, due to new consumer trends and the growth of the beauty industry, specifically the skincare sector. Added to this the characteristics of Amazon beauty secrets water oil, the project is expected to be feasible in the target market.